Molecular characterization of the its2 transcript and saxitoxin biosynthetic genes in two toxic dinoflagellates, alexandrium (dinophyceae) from Malaysia - Hii, Kieng Soon (2012)
The genus Alexandrium is a widely distributed dinoflagellate, and has the ability to produce potent neurotoxins, saxitoxin (STX). Taxonomy of this genus still remains uncertain and species identification is yet confusing. In this study, the second internal transcribed spacer (ITS2) transcript was used to infer the phylogenetic relationships of Alexandrium species distributed worldwide. A total of 33 ITS2 transcript of Alexandrium spp. were successfully modeled in silico, with one each from Pyrodinium bahamense var. compressum, Coolia malayensis and C. monotis as outgroup) The models showed conserved four universal helices of ITS2 transcript. The phylogenetic inference based on sequence-structural information revealed nearly similar phylogenetic framework as inferred in the Large Subunit (LSU) rDNA phylogeny. However, the results showed possible phylogeographic break in the A. minutum Glade where the Asia Pacific and New Zealand A. minutum formed a distant group from the Australian and European group. Genetics of the STX biosynthesis pathway has recently become one of the major focuses in Paralytic Shellfish Poisoning (PSP) toxin-related studies after the discovery of STX biosynethetic genes in toxic cyanobacteria, and later in the toxic dinoflagellates. In the present study, two domains of a saxitoxin biosynthetic gene sxtA, S-adenosyl-L-methionine (SAM)-dependent methyltransferase coding gene (sxtA1) and the class 11 aminotransferase coding gene (sxtA4) were characterized from a toxic A. tamiyavanichii from Samariang, Sarawak. A saxitoxin biosynthetic gene encoding the O-carbamoyltransferase (sxtl) was also characterized in the toxic A. minutum from Tumpat, Kelantan. The partial coding sequences of saxitoxin starting gene, sxtAl and sxtA4 of A. tamiyavanichii were 432 bp and 639 bp, respectively. While the deduced amino acid sequences of sxtAl and sxtA4 were 144 and 213 amino acid residues, respectively. Sequences comparison revealed high similarity and identity to other PSP toxins-producing dinoflagellates (82-98% and 84-99%). In contrast, protein phylogenetic analyses revealed close relationship of both A. tamiyavanichii sxtA1 and sxtA4 to others PSP toxins-producing dinoflagellates, with sxtA of PSP toxins-producing cyanobacteria and putative toxin-related genes forming the sister Glade. On the other hand, the coding sequence of O-carbamoyltransferase (sxtl) of A. minutum was 1,920 bp long, and the deduced amino acid sequence revealed a polypeptide of 639 amino acids. Structural sequence alignment revealed high similarity and identity (50-52% and 87- 89%) to sxd from the toxic cyanobacteria. Sequence comparison of A. minutum sxtl revealed highly conserved pattern, with five phosphorylation motifs, two catalytic regions, and a zinc finger detected. Even though homology between A. minutum sxtl and other cyanobacterial sxtl was observed, protein phylogenetic analysis inferred a distant relationship with the cyanobacterial Sxtl, suggesting a paralog of SxtI in dinoflagellates.